A novel approach to design lesion-specific stents for minimum recoil - Farhan Khan, Muhammad; Brackett, David; Ashcroft, Ian; Tuck, Christopher; Wildman, Ricky D. (American Society of Mechanical Engineers, 2016)
Stent geometries are obtained by topology optimization for minimized compliance under different stenosis levels and plaque material types. Three levels of stenosis by cross-sectional area, i.e., 30%, 40%, and 50% and three different plaque material properties, i.e., calcified, cellular, and hypocellular, were studied. The raw optimization results were converted to clear design concepts and their performance was evaluated by implanting them in their respective stenosed artery types using finite element analysis. The results were compared with a generic stent in similar arteries, which showed that the new designs showed less recoil. This work provides a concept that stents could be tailored to specific lesions in order to minimize recoil and maintain a patent lumen in stenotic arteries.